PERLINDUNGAN HUKUM TERHADAP JUSTICE COLLABORATOR DALAM TINDAK PIDANA NARKOTIKA - Isti Latifah Astri; Sidik Sunaryo; Bayu Dwi Widdy Jatmiko (Universitas Muhammadiyah Malang, 2021)
Justice Collaborator is a new term in the criminal justice process in Indonesia. JusticeCollaborator is a suspect, defendant, or convicted who can cooperate with law enforcement touncover a particular crime. In the context of narcotics crimes, Justice Collaborator has animportant role in uncovering narcotics syndicates because so far there are weaknesses in thecriminal justice system that have not been able to uncover, fight and eradicate crimes of a terrornature. Justice Collaborator is therefore entitled to protection. The purpose of this research isto know the rights and obligations of Justice Collaborator narcotics crimes as well as the policyformulation of legal protection against Justice Collaborator narcotics crimes in the future. Theresearch method used in reviewing this is with a normative juridical approach. The regulationon the protection of Justice Collaborator is set out in Article 5 Paragraph (1), Article 10 andArticle 10A of Law No. 31 of 2014 on The Protection of Witnesses and Victims, while for theobligations stipulated in Article 30 of Law No. 31 of 2014 on The Protection of Witnesses andVictims. But the provision has some drawbacks, especially for Justice Collaborator narcoticscrimes. Therefore, it takes a policy of legal formulation to obtain an ideal form of legalprotection so that the principle of legal certainty can be realized.